Adolescent Sexual Behavior In The Era Of The Industrial Revolution 4.0 - Dewi Andang Prastika; Intan Nugraheni Hasanah (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: The index of adolescent knowledge about reproductive health has increased. Ease of accessing information is an important point in increasing adolescent knowledge about reproductive health, but the use of social media without parental supervision can also lead to risky sexual behavior. In this study, the author aims to determine adolescent knowledge about reproductive health, access to social media as a source of information, and sexual behavior in adolescents in Klaten. Methods: The design in this study is a cross-sectional qualitative research. The population is adolescents aged 16-18 years in the Klaten Regency area. The sample in this study were 96 samples years by using non-probability method sampling count by lemeshow formula selected based on the inclusion and exclusion criteria through youth organizations. The instrument used was questionnaire consist of 4 indicators (usage of social media, source of health reproduction information, knowledge of health reproduction, sex behavior. After validity and reliability test, the questionnaire obtained 30 questions. Data was collected online by using google forms. Analysis data procedure was using chi square and logistic regressionanalysis techniques. Results: The most respondents aged 18 years (48.60%), female gender (88.78%), accessed social media for 7-12 hours as much as 57.01%, all respondents accessed search engines and whatsapp, the majority of respondents received Information about reproductive health from the internet is 90.65%, 59.81% of respondents' parents have a role in discussing reproductive health, 83.18% of respondents have good knowledge about reproductive health, 85.98 % respondents have risky sexual behavior. Conclusion: The role of parents and the duration of adolescents accessing social media has a significant relationship in adolescent sexual behavior.